2018
DOI: 10.6065/apem.2018.23.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Association Kikuchi disease with Hashimoto thyroiditis: a case report and literature review

Abstract: Kikuchi-Fujimoto disease (KFD) is a benign and self-limited disease characterized by fever and lymphadenopathy. The etiology of KFD is unknown, but an autoimmune cause has been suggested. Hashimoto thyroiditis is the most common autoimmune thyroid disorder in children and is known to be associated with other autoimmune diseases. Only a few cases of Hashimoto thyroiditis associated with KFD have been documented. We report a case of a 16-year-old girl who was first diagnosed with KFD and developed Hashimoto thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Hashimoto's thyroiditis has also been associated with Kikuchi disease. In majority of the cases, KFD and Hashimoto's thyroiditis occurred concurrently; however, in three cases, the diagnosis of Hashimoto's thyroiditis preceded that of KFD [24]. Previous reported cases note that it is more common in females and may be positive for ANA, complement, and antiphospholipid antibodies.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Hashimoto's thyroiditis has also been associated with Kikuchi disease. In majority of the cases, KFD and Hashimoto's thyroiditis occurred concurrently; however, in three cases, the diagnosis of Hashimoto's thyroiditis preceded that of KFD [24]. Previous reported cases note that it is more common in females and may be positive for ANA, complement, and antiphospholipid antibodies.…”
Section: Discussionmentioning
confidence: 82%
“…Previous reported cases note that it is more common in females and may be positive for ANA, complement, and antiphospholipid antibodies. Most reported cases complete resolution within a year following supportive care in some patients and steroids in others [24]. We came across a case report of a 17-year-old female with concurrent SLE and Hashimoto's thyroiditis who responded well to steroids and hydroxychloroquine.…”
Section: Discussionmentioning
confidence: 98%
“…Coexisting renal disease is common, with an incidence ranging from 10% to 60%. 4 , 8 , 9 Out of all these associations, the association of KFD with SLE has been the most studied. Dumas et al suggested, KFD may be a clinical feature or an incomplete phase of lupus lymphadenitis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many associations with KFD and other diseases in various case reports in the literature including but not exclusive to hemolytic uremic syndrome, Hashimoto's thyroiditis, hemophagocytic lymphohistiocytosis and more commonly, systemic lupus erythematosus [11][12][13][14][15]. Twin 2 had a background of nephrotic syndrome and celiac disease as discussed above.…”
Section: Discussionmentioning
confidence: 99%